STRUCTURE OF TUNGSTEN OXIDE NANOPARTICLES OBTAINED IN ULTRASONICALLY ASSISTED ELECTRIC DISCHARGE AS STUDIED BY IR AND PL METHODS - Kaptakov, Mikhail; Kohlert, Victoria (Revista Inclusiones, 2020)
In this study, nanoparticles of tungsten oxide with controlled size and shape and narrow particle size distribution synthesized by plasma discharge in the presence of ultrasonic cavitation. Exploration of synthesized nanoparticles has demonstrated that the factor of ultrasonic cavitation during the synthesis substantially affects physical properties of nanoparticles. Defects of crystalline structure governs the luminescence characteristics as well as peculiarities of internal composition of nanoparticles as reflected from IR studies.